Analyzing the technical performance of Swedish farms - Andersson, Per (2014)
This study analyses the technical performance of Swedish farms involved in horse related activities. The technical performance is analyzed by the technical efficiency of the farms and the factors that contribute to technical efficiency. The method used in this study is that of stochastic frontier analysis, where the stochastic frontier production function is estimated in order to obtain the technical efficiency scores of the Swedish farms. The factors that contribute to technical inefficiency are then estimated simultaneously with the stochastic frontier production function in order to see the effect the factors have on the technical performance of the Swedish farms. The relevant data has been collected from a survey implemented and supervised by LRF Konsult and designed by the department of Economics at the Swedish University of Agricultural Sciences. The complete sample data consists of 428 observations, but only 58 are used in the analysis of the technical performance. The output of the Swedish farms consist of income from agricultural production and income from horse related activities. The used by the farms are land, labor, capital and intermediate consumption. The results show that there is no farm that is neither fully efficient nor fully inefficient and where the mean technical efficiency is 0.69. Factors that do contribute to an efficient farm operation that is involved in horse related activities are farmers that receive grants. The factor age does also contribute to technical efficiency where younger farmers tend to be more efficient than older farmers do.